(untitled) (Impetus, 2025)
The physical education class is framed by the relationships between its main actors: students and teachers. However, the social context significantly influences the teaching-learning process. This article presents the results of a study based on educational action research (EAR), in which a didactic unit was implemented with the aim of improving school coexistence in an educational institution located in a vulnerable area of Medellín. The participants included 35 students aged 14 to 15, two subject teachers, and a trainee teacher. The results indicate that enhancing attitudinal content, promoting students as key agents in their own learning, fostering a horizontal teaching environment, adopting a formative and shared evaluation approach, and implementing cooperative methodologies can contribute to improving school coexistence. Finally, the study concludes that the EAR methodology, along with formative evaluation in the classroom, enables continuous reflection on the teaching-learning process and serves as a powerful tool for initial teacher training.